2015
DOI: 10.1186/s13148-015-0109-x
|View full text |Cite
|
Sign up to set email alerts
|

DNA hydroxymethylation age of human blood determined by capillary hydrophilic-interaction liquid chromatography/mass spectrometry

Abstract: BackgroundAging is a complex phenomenon and characterized by a progressive decline in physiology and function of adult tissues. However, it hasn’t been well established of the correlation between aging and global DNA methylation and hydroxymethylation that regulate the growth and development of higher organisms.ResultsWe developed an on-line trapping/capillary hydrophilic-interaction liquid chromatography/electrospray ionization-mass spectrometry method for ultra-sensitive and simultaneous quantification of 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Supporting this idea, we found moderate enrichment of age-related DHMRs at CpG shores, CpG shelves, promoters, 5ʹUTRs, exons, introns, and 3ʹUTRs compared to a random distribution ( Figure S1B). While this enrichment of DHMRs at specific genomic locations was subtle, DHMRs also showed a clear bias toward hypo-hydroxymethylation with age (Table 1), a pattern supported by human studies showing decreased 5hmC levels in blood with age [21,22]. Combined, these data suggest that age-related changes in 5hmC are non-random, and that DNA hydroxymethylation could play a role in the aging process.…”
Section: Discussionmentioning
confidence: 56%
“…Supporting this idea, we found moderate enrichment of age-related DHMRs at CpG shores, CpG shelves, promoters, 5ʹUTRs, exons, introns, and 3ʹUTRs compared to a random distribution ( Figure S1B). While this enrichment of DHMRs at specific genomic locations was subtle, DHMRs also showed a clear bias toward hypo-hydroxymethylation with age (Table 1), a pattern supported by human studies showing decreased 5hmC levels in blood with age [21,22]. Combined, these data suggest that age-related changes in 5hmC are non-random, and that DNA hydroxymethylation could play a role in the aging process.…”
Section: Discussionmentioning
confidence: 56%
“…Accumulated data supported the idea that DNA methylation showed reduced stringency in maintenance over the lifespan, resulting in an increase in inter-individual variability along with the overall decrease in DNA methylation [ 36 ]. Our previous study [ 37 ] also observed a slight negative correlation between 5-mC and chronological age.…”
Section: Discussionmentioning
confidence: 61%
“…The mass spectrometry detection was performed under positive electrospray ionization mode [ 37 ]. The target nucleosides were monitored by multiple reaction monitoring (MRM) mode using the mass transitions (precursor ions ➔ product ions) of dC (228.4 ➔ 112.2), T (243.3 ➔ 127.2), dA (252.4 ➔ 136.2), dG (268.4 ➔ 152.4), rC (244.4 ➔ 112.2), rU (245.4 ➔ 113.1), rA (268.4 ➔ 136.2), rG (284.5 ➔ 152.2), 5-mdC (242.3 ➔ 126.1), and 5-hmdC (258.2 ➔ 142.1).…”
Section: Methodsmentioning
confidence: 99%
“… 40 , 41 Currently, global DNA hydroxymethylation is being characterised as a strong and reproducible trademark of chronological age, potentially acting on the assessment of health and disease prevention. 42 Truong et al 43 recently reported that the level of hydroxymethylation in peripheral blood T cells from humans is dependent on age, and is associated with a gradual decrease of TET3 expression levels during aging. However, in our study, we detected no influence of age on DNA global methylation and hydroxymethylation levels in skin tissue ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%